2017
DOI: 10.5530/jyp.2017.9.23
|View full text |Cite
|
Sign up to set email alerts
|

In silico Docking Studies on ATP-Sensitive K+Channel, Insulin Receptor and Phosphorylase kinase Activity by Isolated Active Principles of Stereospermum tetragonum DC

Abstract: INTRODUCTIONATP-sensitive potassium (K ATP ) channels play a central role in glucosestimulated insulin secretion from pancreatic beta cells. Insulin secretion is initiated by closure of the channels and inhibited by their opening. 1The beta-cell K ATP channel is an octameric complex of four pore-forming, inwardly rectifying potassium-channel subunits (Kir6.2) and four regulatory sulfonylurea-receptor subunits (SUR1). Both Kir6.2 and SUR1 are required for correct metabolic regulation of the channel: ATP closes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Other authors have reported successful computational screening of K + channels. These reports demonstrate that computational screening is an effective method for rapidly discovering new channels blockers from large databases (Kingsley et al, 2017; Liu et al, 2003). Hong Liu and coworkers identified 14 natural compound of relatively lower binding energy.…”
Section: Discussionmentioning
confidence: 88%
“…Other authors have reported successful computational screening of K + channels. These reports demonstrate that computational screening is an effective method for rapidly discovering new channels blockers from large databases (Kingsley et al, 2017; Liu et al, 2003). Hong Liu and coworkers identified 14 natural compound of relatively lower binding energy.…”
Section: Discussionmentioning
confidence: 88%
“…15 Computational methods, such as molecular docking, have been used to predict the molecular mechanism of bioactive compounds at the atomic-level. [16][17][18][19] Therefore, the aims of this work were to study the structure-activity relationship of NaK-ATPase inhibition of three bufadienolides using molecular docking method.…”
Section: Introductionmentioning
confidence: 99%